2023
DOI: 10.1093/oncolo/oyad009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Female Participant Representation in Registered Oncology Clinical Trials in the United States from 2008 to 2020

Abstract: Background Female underrepresentation in oncology clinical trials can result in outcome disparities. We evaluated female participant representation in US oncology trials by intervention type, cancer site, and funding. Materials and Methods Data were extracted from the publicly available Aggregate Analysis of ClinicalTrials.gov database. Initially, 270 172 studies were identified. Following the exclusion of trials using Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This imbalance in gender representation is similar to that reported by the Checkmate-214 trial and it is in line with less than 30% of female patients included in the Keynote-426, Checkmate-9ER, and CLEAR trials [ 5 7 ]. Despite the incidence ratio of RCC in males to females of 2:1 [ 46 ] and the implemented cancer clinical trials in the last 20 years, the issue of under-representation of female patients remains to be addressed [ 47 ]. Considering the gender differences in the immune system, behaviors, and lifestyle, as well as the heterogeneity of efficacy and outcomes with ICI treatment [ 48 ], specific measures such as stratifying patients by gender should be promptly applied in clinical trials [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance in gender representation is similar to that reported by the Checkmate-214 trial and it is in line with less than 30% of female patients included in the Keynote-426, Checkmate-9ER, and CLEAR trials [ 5 7 ]. Despite the incidence ratio of RCC in males to females of 2:1 [ 46 ] and the implemented cancer clinical trials in the last 20 years, the issue of under-representation of female patients remains to be addressed [ 47 ]. Considering the gender differences in the immune system, behaviors, and lifestyle, as well as the heterogeneity of efficacy and outcomes with ICI treatment [ 48 ], specific measures such as stratifying patients by gender should be promptly applied in clinical trials [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research reveals a historical underrepresentation, with only 34.7% of participants in cancer preventive and therapy studies from 1990 to 2001 being female [69]. Though a more recent analysis involving data from 2008 to 2020 showed that females constituted 46.9% of participants in oncologic clinical trials, there were concerning proportional participation rates (PPR) of 0.912 across all trials, with women facing significant underrepresentation in surgical (PPR 0.74) and other invasive (PPR 0.69) oncology trials [70]. Further, recent immunotherapy trials such as the AEGEAN and KEYNOTE671, investigating perioperative chemoimmunotherapy in NSCLC, revealed a stark disparity of approximately 70% of participants in both treatment and placebo arms being male [71,72].…”
Section: Lack Of Inclusion In Clinical Trialsmentioning
confidence: 99%
“…This is similar to cardiology trials (population prevalence ratio, ∼0.7) but markedly worse than oncology trials (population prevalence ratio, 0.9). 6 , 7 …”
mentioning
confidence: 99%